Studi perbandingan mutu kulit jadi (finished leather) yang berasal dari kulit yang diawet dengan garam dan yang diawetkan dengan sinar matahari - Sri Untari; Jayusman Jayusman (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1988)
The object of this study is to obtain the differences glace leather properties made from:a. Sun dried goat skinsb. Wet salted goat skinsc. And preserved for 1, 2 and 3 months successively, the curing and preservation of which is in accordance with BPK (KSI) method.The sample observed is 18 sides goat skins which are taken from a slaughted – house in Yogyakarta. 9 side of those are preserved by sun drying and the rest is wet salted, preserved for 3 months is accordance with BPK/KSI method of preservation.Out of the 1, 2 and 3 months preservation, 1 side of the dried and wet salted skins is taken and processed into glace leather according to BPK method with 2 replications. The tanned leather then is subjected to organoleptic, physical and chemical analyses.The study is carried out in 1 year. The chemical and organoleptic data are obtained from variance sub sample (£ < 0,05) CRD factorial analyses. Whereas the physical properties are analysed by variance sub sample (£ < 0,05) CRD factorial analyses. Whereas the physical properties are analysed by variance sub sample (£ < 0,05) CDR factorial and Duncan’s Test (£ < 0,05).The result of organoleptic analyses show that there is no different properties between glace leather mode from dried and wet salted goat skins (£ < 0,05) and the time of preservation used has no influence on the them (£ < 0,05).But there are differences on tensile strength and stretch properties between glace leather made from dried and wet salted skins (£ < 0,05) and the time of preservation used influnces on the them (£ < 0,05). INTISARI Penelitian ini dimaksudkan untuk mencari jawaban apakah ada perbedaan sifat- sifat kulit glase kambing, yang masing- masing berasal dari kulit mentah diawet dengan cara :Dikeringkan dengan sinar matahariDigaram basahKulit awetan disimpan masing-masing 1 bulan, 2 bulan dan 3 bulan, pengawetan dan penyimpanan sesuai metode BPK (KSI)*Seluruh sampel berjumlah 18 lembar kulit kambing yang berasal dari pemotongan hewan di Yogyakarta. 9 lembar diawet dengan dikeringkan dan 9 lembar dengan digaram basah, disimpan selama 3 bulan menurut BPK / KSI*. Setelah disimpan 1 bulan, 2 bulan, 3 bulan, diambil masing- masing 1 lembar kulit kering dan 1 lembar kulit garaman disamak menjadi kulit glase menurut metode BPK dengan 2 replikasi. Sari hasil penyamakan kemudian masing-masing diuji sifat organoleptis, fisis dan kimiawi.Penelitian di lakukan selama 1 tahun. Analisa data untuk pengujian organoleptis dan kimiawi dengan analisa varians sub sampel (P < 0,05) dengan CDR faktorial. Sedangkan untuk pengujian dengan analisa varian sub sampel (P < 0,05) sengan CDR faktorial dan Ducan’s Test (P < 0,005). Hasil penelitian menunjukkan bahwa untuk pengujian organoleptis tidak asa perbedaan, antara kulit kering dan kulit garaman (P < 0,05), dan tidak ada pengaruh lama penyimpanan ( P < 0,005). *BPK = Balai Penelitian Kulit*KSI = Kulit Standar Industri